2004
DOI: 10.1073/pnas.0408229102
|View full text |Cite
|
Sign up to set email alerts
|

Caspases and nitric oxide broadly regulate dendritic cell maturation and surface expression of class II MHC proteins

Abstract: The passage of dendritic cells (DC) from immature to terminally differentiated antigen-presenting cells is accompanied by numerous morphological, phenotypic, and functional changes. These changes include, for example, expression of ''empty'' class II MHC proteins (MHCII) at the surface in immature DC, whereas a much larger amount of peptide-loaded MHCII is expressed at the surface in mature DC. Here we show that, in cultured immature DC derived from murine bone-marrow precursors, a number of molecules involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 49 publications
4
42
0
Order By: Relevance
“…Caspases have been found to cleave the AP-1 and AP-2 proteins that play an important role in trafficking of MHC class II molecules, which traverse through at least some of the same endocytic compartments as CD1d molecules. 45 Interestingly, and similar to CD1d, we found that camptothecin treatment also inhibits MHC class II-mediated antigen presentation (data not shown). Furthermore, CD1d/LAMP-1 co-localization (%) * *** Figure 6.…”
Section: Discussionmentioning
confidence: 70%
“…Caspases have been found to cleave the AP-1 and AP-2 proteins that play an important role in trafficking of MHC class II molecules, which traverse through at least some of the same endocytic compartments as CD1d molecules. 45 Interestingly, and similar to CD1d, we found that camptothecin treatment also inhibits MHC class II-mediated antigen presentation (data not shown). Furthermore, CD1d/LAMP-1 co-localization (%) * *** Figure 6.…”
Section: Discussionmentioning
confidence: 70%
“…NO then further inhibits caspases and enhances NOS2 expression and NO synthesis in mature DC. We have shown previously that inhibition of caspases by NO upregulates expression of CD74 (Huang et al, 2008) and other endosomal proteins (Wong et al, 2004;Santambrogio et al, 2005), which is essential for regulating the MHC IIrestricted antigen presentation pathway. This subsequently enhances the capability of DC in inducing T cell proliferation/ activation.…”
Section: Discussionmentioning
confidence: 98%
“…N9, a wellcharacterized murine microglial cell line was a kind gift from Dr. Ricciardi-Castagnoli. Bone marrow-derived DC from 6-to 7-week-old C57BL/6J mice was established by the bulk-culture method as previously described (Wong et al, 2004). Briefly, bone-marrow cells were harvested from the long bones and plated on dishes in complete DMEM with 10% FCS containing 20 ng/mL of mouse recombinant GM-CSF (R&D Systems, USA).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This minor peptide loading pathway depends on the presence of extracellular proteases capable of processing Ags. In immature DCs, one can speculate that the caspase-mediated inactivation of AP-2, the adaptor protein complex that mediates internalization of proteins with tyrosine-based sorting motifs, causes the accumulation of DM at the plasma membrane (13). On maturation, internalization of DM to endocytic compartments resumes and most MHC II become filled with peptides (11).…”
Section: A Lthough Immunization With Tumor Ags Can Activatementioning
confidence: 99%